2016
DOI: 10.1111/1742-6723.12617
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric recreational vehicle‐related head injuries presenting to the emergency department of a major paediatric trauma centre in Australia: Is there room for improvement?

Abstract: RV-related HIs accounted for a non-negligible proportion of paediatric HIs presenting to the ED and for significant morbidity and use of hospital resources. Interventions such as introduction of mandatory helmet use for off-road motorised vehicle riding and skateboard riding in children, enhanced injury prevention campaigns, and strict adult supervision during motorised vehicle riding may reduce the morbidity and health care costs associated with paediatric RV-related HIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…However, the use of helmets has been shown to reduce risk of death in both motorised and non-motorised accidents related to the use of recreational vehicles. (15,16) Our research shows the need for greater helmet safety for PMD users as well. On the other hand, abdominal, pelvic and spinal injuries were very uncommon (one patient in each category).…”
Section: Discussionmentioning
confidence: 85%
“…However, the use of helmets has been shown to reduce risk of death in both motorised and non-motorised accidents related to the use of recreational vehicles. (15,16) Our research shows the need for greater helmet safety for PMD users as well. On the other hand, abdominal, pelvic and spinal injuries were very uncommon (one patient in each category).…”
Section: Discussionmentioning
confidence: 85%
“…This is a potentially modifiable cause of injury. Research has shown the positive impact simple interventions such as helmet use can have on WNMV-associated injuries [18,19]. Currently, Ireland has no injury prevention/ safety legislation related to these vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…Falls from scooters were a common mechanism causing head injury, particularly among females. Scooters are a popular non‐motorised wheeled device, which are commonly used without helmets . Helmets are not compulsory during scooter use in Australia .…”
Section: Discussionmentioning
confidence: 99%
“…Scooters are a popular non‐motorised wheeled device, which are commonly used without helmets . Helmets are not compulsory during scooter use in Australia . There is, however, strong evidence that helmets reduce the risk of head injuries during pedal cycle crashes, and therefore, helmets may have application to preventing head injury among scooter users .…”
Section: Discussionmentioning
confidence: 99%